The Influence of the PBL Model Assisted by Lectora Inspire 18 Dynamic Fluid Material on Mastery of the Concept of SMAN 3 Jember - Silvira, Lia; Mahardika, I Ketut; Maryani, Maryani (Universitas Negeri Padang, 2023)
In the era of the 21st century, the transformation of learning that focuses on the role of teachers into a focus on active student engagement is essential. Lack of mastery of concepts by students is often influenced by the selection of learning models and media that are less supportive, resulting in less responsiveness of students to the learning process. The purpose of this study was to examine the effect of the PBL model assisted by Lectora Inspire 18 dynamic fluid material on mastery of physics concepts. This research is an experimental research with pretest-posttest control group design. Data collection methods consist of writtent tests. Data analysis techniques for mastering concepts use the Mann Withney U Test, while critical thinking skills use score criteria. The results showed Asymp.Sig. (2-tailed) of 0.000 (<0.05). The conclusion obtained is that there is a significant influence on the application of the PBL model assisted by Lectora Inspire 18 dynamic fluid material on mastery of physics concepts